2013
DOI: 10.1007/s11431-013-5336-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of solid particle clusters in coherent structures of turbulent channel flow

Abstract: A particle-laden turbulent channel flow is investigated to study particle clusters in large-scale turbulent coherent structures. The fluid phase is calculated by large eddy simulation and particles are tracked using Lagrangian trajectory method. The flow Reynolds number is 180 based on the friction velocity and half-width of the channel. The particle is lycopodium with St=0.93 which may well follow the fluid phase. The mean and fluctuating velocities of both two phases are obtained, which are in good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[1][2][3] It is also the foundation of gas-particle twophase turbulent combustion in many industrial processes. [4,5] Therefore, it is vital to understand the processes and mechanisms of particle dispersion and transport in turbulent airflows to apply industry controls and improve combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It is also the foundation of gas-particle twophase turbulent combustion in many industrial processes. [4,5] Therefore, it is vital to understand the processes and mechanisms of particle dispersion and transport in turbulent airflows to apply industry controls and improve combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of fluid motion on aerosol particle behavior is crucial in predicting particle dispersion and transport. [5] Traditional theories assume that particles are randomly distributed in turbulent flows according to the diffusion of passive scalars. However, Crowe et al, Squires and Eaton, and Wang and Maxey have found that there are highly nonuniform concentration distributions of particles in turbulent flow fields.…”
Section: Introductionmentioning
confidence: 99%